PENGARUH CURRENT RATIO, QUICK RATIO DAN TATO TERHADAP LABA BERSIH PT. INDOSAT TBK PERIODE 2005-2013 - Susilawati Susilawati; Fadil Iskandar (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2015)
The main objective of the company is generating profits, net income is an importantindicator which should be noted by the management of the company to assess the level of success or the health of the company. The data used are of financial statements and annual report PT Indosat Tbk from 2005 until the year 2013, published through the website www.indosat.com. This research consists of variable current ratio (X 1), quick ratio (X 2), and tattoos (X 3) as the independent variable and the dependent variable as net profit. The results of this research is the third free variables there is a significant impact against net profit together and only partial TATTOOS that have significant effects on income bersigh, evident from the R-square is only 76.9% of the variation in net profit can be explained by the variation of current ratio, quick ratio and tattoos, while 13.1% the rest is explained by factors outside of research. It was concluded that current ratio, quick ratio and a TATTOO carries a significant impact against net income, as seen in F-test where F calculate > F table and t-test where t calculate > t table.Keyword: current ratio, quick ratio, tattoos